2014
DOI: 10.1039/c4tc02119c
|View full text |Cite
|
Sign up to set email alerts
|

TransCap: a monolithically integrated supercapacitor and electrolyte-gated transistor

Abstract: We report the proof-of-concept of the TransCap, a monolithically integrated device that exhibits the storage properties of a supercapacitor and the low-voltage operation of an electrolyte-gated transistor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…For the different EGTs here considered up to 50% of the energy spent to drive the EGT can be stored (E stored  = 100 Egs/E EGT ), and thus, saved (Table S1). More importantly, these results point to the integration of EGT and μSCs at materials level, which has been demonstrated with TransCap [27]. TransCap featured an MEHPPV channel, a gate based on commercial activated carbon layer deposited on carbon paper and the ionic liquid N 1113 TFSI.…”
Section: Introductionmentioning
confidence: 73%
“…For the different EGTs here considered up to 50% of the energy spent to drive the EGT can be stored (E stored  = 100 Egs/E EGT ), and thus, saved (Table S1). More importantly, these results point to the integration of EGT and μSCs at materials level, which has been demonstrated with TransCap [27]. TransCap featured an MEHPPV channel, a gate based on commercial activated carbon layer deposited on carbon paper and the ionic liquid N 1113 TFSI.…”
Section: Introductionmentioning
confidence: 73%
“…We have recently demonstrated that electrolyte‐gated transistors based on organic polymers can be also exploited for energy storage purposes into a novel device structure named transcap (transistor‐capacitor) . This device exploits the high pseudocapacitance and capacitance displayed by organic conducting polymers and high surface area carbons at the interface with an electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…This device exploits the high pseudocapacitance and capacitance displayed by organic conducting polymers and high surface area carbons at the interface with an electrolyte. Specifically, transcaps combine charge transport and charge storage features to yield a low‐energy cost device that can drive/power additional elements . We fabricated transcaps on rigid substrates and employing the organic semiconductor poly[2‐methoxy‐5‐(20‐ethylhexyloxy)−1,4‐phenyl‐ene vinylene (MEH PPV) as the channel material, the ionic liquid 1‐Ethyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIM TFSI) as the electrolyte and activated carbon on carbon paper as the gate, in a stacked configuration .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slow component of the time response is comparable to other electrolyte gated devices. [15,17] To check the behavior of the slow response with temperature, we measured the electrical properties of graphene using a cryostat partially evacuated with a rotary pump (Figure 2f). …”
mentioning
confidence: 99%